Stellar spectra analysis of giant stars: ARCTURUS - Rah, Maria
In this study, we analyzed the evolved red giant ARCTURUS using high-resolution spectroscopy that was taken by HARPS. The other names of this star is α Boo - Arcturus - HR 5340-HD 124897- HIP 69673. This evolved (log g = 1.66 dex) star shows low metallicity nature ([Fe/H] = -0.52) which could be employed to study the chemical evolution of the early universe.
Keywords: Astronomy